PREGNANCY AFTER KIDNEY TRANSPLANT - Huamán G., Moisés (2015)
We studied 8 women transplanted kidney, who completed 10 pregnancies. All grafts were from living persons and 75% were family. The age of pregnant women ranged between 17 and 33 years. The interval between the graft and the pregnancy was 4 months to 5 years, in 3 cases less than one year. Immunosuppression during pregnancy was performed with prednisone (0.15 to 0.20 mglKgldía) and Azothioprina (1.5 to 2.0 mgldía). The most frequent maternal complications were pregnancy-induced hypertension (7 cases), including one case of eclampsia. It was high incidence of urinary tract infection (3 cases), and hydronephrosis, negative factors in the future of the graft. decreased renal function in 2 cases reversible acute rejection and in 1 case was detected. The delivery was by Caesarean section seven cases, a figure that we consider high and may decrease in the future. Delivery implemented to shorten the second is suggested. In four cases bilateral salpingectomy was performed at the request of the couple. Four of the babies are premature. With the exception of a baby to term, all had adequate weight for gestational age. There were 3 cases moderate hypoxia, metabolic disturbances in two acute diarrhea in two other cases. No birth defects were detected.